DOC:NO3− ratios and NO3− uptake in forested headwater streams. Issue 1 (21st January 2016) - Rodríguez‐Cardona, Bianca; Wymore, Adam S.; McDowell, William H.
Abstract: The underlying mechanisms driving the coupled interactions between inorganic nitrogen uptake and dissolved organic matter are not well understood, particularly in surface waters. To determine the relationship between dissolved organic carbon (DOC) quantity and nitrate (NO3 − ) uptake kinetics in streams, we performed a series of NO3 − Tracer Additions for Spiraling Curve Characterization experiments in four streams within the Lamprey River Watershed, New Hampshire, across a range in background DOC concentrations (1–8 mg C/L). Experiments were performed throughout the 2013 and 2014 growing seasons. Across streams and experimental dates, ambient uptake velocity ( V f ) correlated positively with increasing DOC concentrations and DOC:NO3 − ratios but was only weakly negatively associated with NO3 − concentrations. Ambient NO3 − V f was unrelated to pH, light, temperature, dissolved oxygen, and Specific Ultraviolet Absorbance at 254 nm. Although there were general tendencies across the entire Lamprey River Watershed, individual sites behaved differently in their uptake kinetics. NO3 − uptake dynamics in the Lamprey River Watershed are most strongly influenced by DOC concentrations rather than NO3 − concentrations or physicochemical parameters, which have been identified as regional‐ to continental‐scale drivers in previous research. Understanding the fundamental relationships between dissolved organic matter and inorganic nutrients will be important as global and climatic changes influence the delivery and production of DOC and NO3 − in aquatic ecosystems. Key Points: Carbon and nitrogen cycling coupled in streams Higher DOC:NO3 − ratios and DOC concentrations promote the greatest nitrate uptake Biostimulation model in high‐nitrate streams